Negation as a stylistic feature of Ibn al-Hajjaj’s arguments - Ali, Amina; Ali , Fatima (Al-Adab Journal, 2025)
This research is entitled (Negation as a stylistic feature of Ibn Al-Hajjaj’s argumentation) regarding the phenomenon of negation and its argumentative effect in convincing the addressee. Negation is a linguistic phenomenon that means informing about leaving the action, and is linked to certain and each of these tools has (لا، لن، لم، ما، لما، ليس) tools such as Its own meaning. Negation is divided into two parts: explicit negation - implicit negation. In this research, we will limit ourselves to shedding light on the tools that benefit from explicit negation. And its various mechanisms in Ibn Al-Hajjaj’s poetry, and how he employed these links to form a starting point and an outlet through which he presents his evidence and arguments to convince the addressee.